Surgical Management of Local Recurrences of Renal Cell Carcinoma. (26th January 2016) - Acar, Ömer; Şanlı, Öner
Abstract : Surgical resection either in the form of radical nephrectomy or in the form of partial nephrectomy represents the mainstay options in the treatment of kidney cancer. In most instances, resecting the tumor bearing kidney or the tumor itself provides durable cancer specific survival rates. However, recurrences may rarely develop in the renal fossa or remnant kidney. Despite its rarity, locally recurrent RCC is a challenging condition in terms of the possible management options and relatively poor prognosis. If technically feasible, wide surgical excision and ensuring negative surgical margins are the most effective treatment options. Repeat surgeries (completion nephrectomy, excision of locally recurrent tumor, or repeat partial nephrectomy) may often be complicated, and perioperative morbidity is a major concern. Open approach has been extensively applied in this context and 5-year cancer specific survival rates have been reported to be around 50%. The roles of minimally invasive surgical options (laparoscopic and robotic approach) and nonsurgical alternatives (cryoablation, radiofrequency ablation) have yet to be described. In selected patients, surgical resection may have to be complemented with (neo)adjuvant radiotherapy or medical treatment.